USE OF COMPUTER ALGEBRA SYSTEM MAXIMA IN THE PROCESS OF TEACHING FUTURE MATHEMATICS TEACHERS - Velychko, Vladyslav Ye; Stopkin, Andrii V.; Fedorenko, Olena H. (Information technologies and learning tools, 2019)
The article is devoted to the research of a problem of the application of computer algebra systems in the course of skill training of future mathematics teachers. The possibility of study organization for students of pedagogical institutions of higher education receiving "014 secondary education (mathematics)" speciality with the use of computer algebra systems is considered. The term "computer algebra system" is understood as the software which is intended for the solving of various mathematical tasks by means of a computer with a possibility of visualization of all stages of calculations. Proceeding from the fact that the computer algebra systems are actively used in educational process all over the world and informational educational environments in the course of teaching mathematical disciplines are created on their basis, it is possible to make a conclusion that the computer algebra systems are very important components of the process of training future experts. The current state of the problem of introduction and application of the computer algebra systems in the training of future mathematics teachers is investigated. The role of the computer algebra systems in teaching mathematics subjects and general natural sciences in pedagogical establishments of higher education is defined. Such computer algebra systems as MathCAD, MatLab, Maple, Mathematica, Maxima, SAGE, and Axiom are marked out among the most modern and successfully used systems aimed at solving mathematical tasks. Arguments in favour of the use of the free computer algebra system Maxima in educational and scientific activity of students are adduced in the article. Its main advantages and disadvantages are presented. The main functional of this system is considered which allows to optimize the time of the solution of various mathematical tasks, to adjust a conclusion of the received result, to perform staged verification of correctness of calculations.